Gender and Politics in Early Modern Europe - Walker, C. author. aut Link
XII, 247 p.
Keywords: This timely study analyses the seventeenth-century revival of monasticism by English women who founded convents in France and the Low Countries. Examining the nuns' membership of both the English Catholic community and the continental Catholic Church, it argues that despite strict monastic enclosure and exile, they nevertheless engaged actively in the spiritual and political controversies of their day. The book will add much to our understanding of women's power in early modern Europe, and offer an insight into a previously ignored section of English society.